A renewable integrated multi-area system for LFC incorporating electrical vehicle with SoC estimation - Lalhmangaihzuala, F.; Datta, Subir; Lalngaihawma, Samuel; Ustun, Taha Selim; Kalam, Akhtar (Frontiers in Energy Research, 2025)
In this paper, the effect of electric vehicles (EVs) on load frequency control (LFC) in the context of a deregulated market within an asymmetric three-area system featuring a novel combination of hybrid power plants is presented. The paper discusses load frequency control within a deregulated market in an unequal three-area system using a new combination of hybrid power plants. All the areas have one renewable energy source and a thermal power plant (TPP), and each area incorporates electric vehicles. Area 1 contains a combination of a wind turbine system (WTS) and thermal, Area 2 has a geothermal power plant (GTPP) and thermal, and Area 3 has a biogas power plant (BPP) and thermal. This proposed system is investigated. Conventional PID, PI, and I controllers are used because they are simple, cheap, and easily available. Their performance is observed and compared. The controller parameters undergo optimization by applying an innovative optimization method called the Mine Blasting algorithm, which utilizes an integral square error (ISE)-based fitness function. The analysis is done under bilateral and contract violation cases with and without generation rate constraints. Moreover, the state of charge (SoC) estimation concept under a deregulated environment and the significance of EVs in the proposed system, especially in the case of contract violation, is presented.